Variable microstructural response of baddeleyite to shock metamorphism in young basaltic shergottite NWA 5298 and improved U-Pb dating of Solar System events - Darling, James; Moser, Desmond E.; Barker, Ivan R.; Tait, Kim T.; Chamberlain, Kevin R.; Schmitt, Axel Karl; Hyde, Brendt C. (Earth and planetary science letters, 2016)
The accurate dating of igneous and impact events is vital for the understanding of Solar System evolution, but has been hampered by limited knowledge of how shock metamorphism affects mineral and whole-rock isotopic systems used for geochronology. Baddeleyite (monoclinic ZrO2) is a refractory mineral chronometer of great potential to date these processes due to its widespread occurrence in achondrites and robust U-Pb isotopic systematics, but there is little understanding of shock-effects on this phase. Here we present new nano-structural measurements of baddeleyite grains in a thin-section of the highly-shocked basaltic shergottite Northwest Africa (NWA) 5298, using high-resolution electron backscattered diffraction (EBSD) and scanning transmission electron microscopy (STEM) techniques, to investigate shock-effects and their linkage with U-Pb isotopic disturbance that has previously been documented by in-situ U-Pb isotopic analyses. The shock-altered state of originally igneous baddeleyite grains is highly variable across the thin-section and often within single grains. Analyzed grains range from those that preserve primary (magmatic) twinning and trace-element zonation (baddeleyite shock Group 1), to quasi-amorphous ZrO2 (Group 2) and to recrystallized micro-granular domains of baddeleyite (Group 3). These groups correlate closely with measured U-Pb isotope compositions. Primary igneous features in Group 1 baddeleyites (n=5) are retained in high shock impedance grain environments, and an average of these grains yields a revised late-Amazonian magmatic crystallization age of 175±30 Ma for this shergottite. The youngest U-Pb dates occur from Group 3 recrystallized nano- to micro-granular baddeleyite grains, indicating that it is post-shock heating and new mineral growth that drives much of the isotopic disturbance, rather than just shock deformation and phase transitions. Our data demonstrate that a systematic multi-stage microstructural evolution in baddeleyite results from a single cycle of shock-loading, heating and cooling during transit to space, and that this leads to variable disturbance of the U-Pb isotope system. Furthermore, by linking in-situ U-Pb isotopic measurements with detailed micro- to nano-structural analyses, it is possible to resolve the timing of both endogenic crustal processes and impact events in highly-shocked planetary materials using baddeleyite. This opens up new opportunities to refine the timing of major events across the Solar System.